The mediating effect of self-concept in the relationships between attachment, social support and global self-growth among adolescents - Chua, Yee Chii (2018)
Previous studies have posed different roles of self-concept, attachment, and social support to adolescents' global self-worth. But, little known about the relatively significant for each of the variance they may share. The present study starts from the premise to identify the mediating role of self-concept in the relationships between social support and global self-worth among adolescents. Further, this study aims to determine whether adolescents' global self-worth can be predicted through perceived attachment and social support from the parents, peers, and teachers. A self-report survey was administrated to a group of adolescents (N=594) with age ranging from 13 to 18 years; selected using the purposive cluster sampling technique. The locations of the current research were conducted at three main districts of Sabah (Kota Kinabalu, Sandakan, and Tawau). Four scales were used for data collection: The Revised Inventory of Parent and Peer Attachment (IPPA-R; Gullone & Robinson, 2005), Psychological Sense of School Membership (PSSM) (Goodenow, 1993), Social Support Scale for Children and Adolescent (SSSCA) and Self-Perception Profile for Adolescents (SPPA) developed by Harter (2012). PLS-SEM was used as a data analysis technique in the study. The finding showed significant complete mediation role of self-concept between the relationship of teacher support and global self-worth. Additionally, the result also showed significant partial mediation role of self-concept between the influences of parent and peers support on global self-worth among adolescents. Results were discussed with respect to potential mechanisms through which self-concept, attachment, social support and global self-worth may operate. The implications of the study and recommendation for future research are presented.